The Therapeutic Effect of SCFA-Mediated Regulation of the Intestinal Environment on Obesity - You, Huimin; Tan, Yue; Yu, Dawei; Qiu, Shuting; Bai, Yan; He, Jincan; Cao, Hua; Che, Qishi; Guo, Jiao; Su, Zhengquan (Frontiers in Nutrition, 2022)
Intestinal environment disorder is a potential pathological mechanism of obesity. There is increasing evidence that disorders in the homeostasis of the intestinal environment can affect various metabolic organs, such as fat and liver, and lead to metabolic diseases. However, there are few therapeutic approaches for obesity targeting the intestinal environment. In this review, on the one hand, we discuss how intestinal microbial metabolites SCFA regulate intestinal function to improve obesity and the possible mechanisms and pathways related to obesity-related pathological processes (depending on SCFA-related receptors such as GPCRs, MCT and SMCT, and through epigenetic processes). On the other hand, we discuss dietary management strategies to enrich SCFA-producing bacteria and target specific SCFA-producing bacteria and whether fecal bacteria transplantation therapy to restore the composition of the gut microbiota to regulate SCFA can help prevent or improve obesity. Finally, we believe that it will be of great significance to establish a working model of gut– SCFA– metabolic disease development in the future for the improvement this human health concern.